The Pleasure of Being Involved. - Geerling, Let (Rotterdam : Stichting Kaus Australis, 1991)
Bezemer, Nic ; Bragdon, Jonathan ; Breedveld, Marian ; Cuijpers, Mathilde ; Eigenheer, Marianne ; van Mulligen, Chris ; van der Pennen, Hans ; Postema, Dick ; van Rijn, Jeroen ; Roosen, Maria ; Rotmeijer, Peter ; Roy, George le ; Vinken, Jeroen ; Vroegindeweij, Leo ; Wisman, Bert
The Pleasure of Being Involved, Stichting Kaus Australis, Rotterdam, 28 september - 20 oktober 1991
Nederlands & Duits
kunstcatalogus